Pengaruh Perkembangan Peer-to-Peer Lending terhadap Penyaluran Kredit Bank KBMI 1 di Indonesia - Putti Tara Aliffia; Tyas Danarti Hascaryani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The rapid growth of peer-to-peer (P2P) lending in Indonesia raises questions about its impact on banking intermediation, particularly in Bank KBMI 1. This study analyzes the effect of P2P lending growth on Bank KBMI 1 credit growth using monthly data from October 2021 to June 2025 and the Autoregressive Distributed Lag (ARDL) method. The results indicate that P2P lending outstanding and the number of borrowers have no significant long-run effect on credit growth, although they are associated with short-run financing dynamics. Meanwhile, third-party funds and inflation positively and significantly affect credit growth, whereas the BI7DRR has no significant effect. These findings suggest that P2P lending has not replaced the intermediation role of Bank KBMI 1 but instead tends to develop alongside the banking sector in meeting financing needs.